2011
DOI: 10.1029/2011jc007359
|View full text |Cite
|
Sign up to set email alerts
|

Interior versus boundary mixing of a cold intermediate layer

Abstract: [1] The relative importance of interior versus boundary mixing is examined for the erosion of the cold intermediate layer (CIL) of the Gulf of St. Lawrence. Based on 18 years of historical temperature profiles, the seasonal erosion of the core temperature, thickness and heat content of the CIL are, respectively, _ T min = 0.24 ± 0.04°C mo −1 , _ d min = −11 ± 2 m mo −1 and _ H = 0.59 ± 0.09 MJ m −3 mo −1 . These erosion rates are remarkably well reproduced with a one-dimensional vertical diffusion model fed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 36 publications
(57 reference statements)
4
38
0
Order By: Relevance
“…This interval has also been chosen to represent the flux at the base of the euphotic zone, typically found at a depth of 10-20 in the LSLE [Therriault and Levasseur, 1985;Vezina, 1994 Note that for fluxes calculations at Station 23, the diffusivity profiles used are from the station itself, i.e., far from the channel sloping boundaries. As suggested by Cyr et al [2011], the fluxes reported for this station could be increased by 60% to account for boundary mixing processes. Figure 10 (bottom inset) suggests that the observations at the HLC are biased within a semidiurnal cycle, with more observations in the reversal phase near the high tide (t HT 5 0 h).…”
Section: 1002/2014jc010272mentioning
confidence: 61%
“…This interval has also been chosen to represent the flux at the base of the euphotic zone, typically found at a depth of 10-20 in the LSLE [Therriault and Levasseur, 1985;Vezina, 1994 Note that for fluxes calculations at Station 23, the diffusivity profiles used are from the station itself, i.e., far from the channel sloping boundaries. As suggested by Cyr et al [2011], the fluxes reported for this station could be increased by 60% to account for boundary mixing processes. Figure 10 (bottom inset) suggests that the observations at the HLC are biased within a semidiurnal cycle, with more observations in the reversal phase near the high tide (t HT 5 0 h).…”
Section: 1002/2014jc010272mentioning
confidence: 61%
“…For the rest of the year, the system is stratified into three water masses after a surface layer is formed as a result of the spring freshet and increasing air temperature. The previous winter surface layer then becomes trapped as a CIL between two warmer layers (e.g., El-Sabh, 1979;Koutitonsky and Bugden, 1991;Galbraith, 2006;Smith et al, 2006;Cyr et al, 2011). Once regenerated during the winter, the CIL properties are slowly eroded during summer months as a result of mixing (in the estuary, its core temperature warms at a rate of ∼ 0.24 • C per month while its thickness decrease at a rate of ∼ 11 m per month; Gilbert and Pettigrew, 1997;Cyr et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
“…The previous winter surface layer then becomes trapped as a CIL between two warmer layers (e.g., El-Sabh, 1979;Koutitonsky and Bugden, 1991;Galbraith, 2006;Smith et al, 2006;Cyr et al, 2011). Once regenerated during the winter, the CIL properties are slowly eroded during summer months as a result of mixing (in the estuary, its core temperature warms at a rate of ∼ 0.24 • C per month while its thickness decrease at a rate of ∼ 11 m per month; Gilbert and Pettigrew, 1997;Cyr et al, 2011). Because of winter low surface layer salinities in the LSLE that inhibit mixing and convection, the CIL is not formed there but is rather advected from the Gulf during the summer months as the result of the estuarine circulation (e.g., Galbraith, 2006;Smith et al, 2006).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations